1995
DOI: 10.1128/mcb.15.9.4754
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Acidic Phosphoproteins P1 and P2 Are Not Required for Cell Viability but Regulate the Pattern of Protein Expression in Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae strains with either three inactivated genes (triple disruptants) or four inactivated genes (quadruple disruptants) encoding the four acidic ribosomal phosphoproteins, YP1␣, YP1␤, YP2␣, and YP2␤, present in this species have been obtained. Ribosomes from the triple disruptants and, obviously, those from the quadruple strain do not have bound P proteins. All disrupted strains are viable; however, they show a cold-sensitive phenotype, growing very poorly at 23؇C. Cell extracts from the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
149
2
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(166 citation statements)
references
References 33 publications
13
149
2
2
Order By: Relevance
“…In yeast, ribosomes from stationary phase are deficient in P-proteins when compared with those from exponentially growing cells (63). By using cell-free lysates, it was demonstrated that yeast ribosomes lacking P-proteins translated particular mRNAs differentially as compared with ribosomes containing P-proteins (64). The addition of exogenous P-proteins to lysates lacking them abrogated the specific translational differences, suggesting that differences in translation efficiency are attributable to heterogeneity in the P-proteins.…”
Section: Potential Effects Of Ribosome Heterogeneity On the Filtermentioning
confidence: 94%
“…In yeast, ribosomes from stationary phase are deficient in P-proteins when compared with those from exponentially growing cells (63). By using cell-free lysates, it was demonstrated that yeast ribosomes lacking P-proteins translated particular mRNAs differentially as compared with ribosomes containing P-proteins (64). The addition of exogenous P-proteins to lysates lacking them abrogated the specific translational differences, suggesting that differences in translation efficiency are attributable to heterogeneity in the P-proteins.…”
Section: Potential Effects Of Ribosome Heterogeneity On the Filtermentioning
confidence: 94%
“…In comparison, the general tendency of the ribosomal proteins is very different, since the various spots belonging to a distinct gene, are generally distributed evenly in the horizontal direction (Figure 2), indicating a change only in their pI and not in their MW. An exception is the slightly different pattern observed for the ribosomal proteins P1, P2 and P3, which are collectively referred to as stalk proteins because they form a stalk-like protrusion on the large subunit (reviewed by Ballesta and Remacha, 1996) and have been reported to be modified in yeast (Remacha et al, 1995). This is seen particularly for the spot identified as P2 (compare for example the spots for the P2 protein (caption in Figure 1B) with the ones for the S27, L11 or L5 proteins (Figure 2)).…”
Section: Detecting Proteins That Associate With the Plant Ribosomementioning
confidence: 99%
“…We suggest that the excess of Rpp0 may affect transcription by participating in it either directly or indirectly. The latter opportunity is related to the observation that the lack of acidic ribosomal proteins Rpp1A/B and Rpp2A/B, structurally and functionally related to Rpp0, significantly affected the expression of many proteins and chaperones in particular (46). It was proposed that the altered content of acidic proteins in ribosome changed its specificity toward different mRNAs.…”
Section: Non-chaperone Proteins Curing [Psi ϩmentioning
confidence: 99%